A Cross-Cultural/National Study of Canadian, Chinese, and Japanese University Students' Leisure Satisfaction and Subjective Well-Being. (4th March 2017) - Ito, Eiji; Walker, Gordon J.; Liu, Huimei; Mitas, Ondrej
ABSTRACT: The purpose of this study was to examine whether Canadian, Chinese, and Japanese university students' leisure satisfaction affected their subjective well-being (SWB) and, if so, how this process was similar and different cross-culturally/nationally. A series of stepwise multiple regressions indicated that, in general, satisfying leisure significantly and positively impacted SWB across all three cultures, but there were also differences between (a) Canada and both China and Japan in terms of aesthetic leisure satisfaction and (b) China and Japan in terms of psychological and physiological leisure satisfaction. Overall, our results suggest that while satisfying leisure significantly, positively, and substantively impacts SWB in both Western and East Asian cultural contexts, culture frequently influences which specific elements are pertinent. This cross-cultural/national study has important theoretical and practical implications for the currently Western-centric leisure literature and for the understanding of the different roles leisure plays in enhancing SWB across cultures, respectively.